1983
DOI: 10.1017/s0033822200005622
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Gaseous 12CO2, 13CO2, and 14CO2 in the Sub-Soil Unsaturated Zone of the Western US Great Plains

Abstract: Data on the depth distribution of the major atmospheric gases and the abundance of gaseous 12CO2, 13CO2, and 14CO2 in the subsoil unsaturated zone have been obtained from several sites in the western Great Plains of the United States. Sample profiles range from land surface to depths of 50m. Although each site must be considered on an individual basis, several general statements can be made regarding the profiles. 1) Diffusion of these gaseous molecules through the unsaturated zone is an important transport me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
39
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 12 publications
6
39
0
Order By: Relevance
“…Other assumed parameters used in our model calculation are listed in Table 2. In their study, THORSTENSON et al ( 1983) concluded that the measured 14C0, profiles cannot be readily explained with a diffusion model due to some as yet unexplained mechanisms. However, Fig.…”
Section: Observations In Soilsmentioning
confidence: 97%
See 3 more Smart Citations
“…Other assumed parameters used in our model calculation are listed in Table 2. In their study, THORSTENSON et al ( 1983) concluded that the measured 14C0, profiles cannot be readily explained with a diffusion model due to some as yet unexplained mechanisms. However, Fig.…”
Section: Observations In Soilsmentioning
confidence: 97%
“…In Fig. 4, the 14C data (reported as A 14C, percent modem carbon (pmc) = (6'4C/1000 + 1)(1 -2*(25 + 6 13C)/ lOOO)* 100) for soil CO2 and CO2 concentrations (data obtained in May) from site #6 in HAAS et al ( 1983) and THORSTENSON et al ( 1983) are plotted (different symbols represent different sampling dates) and compared to our model calculation (solid line). Since there were no "Co.m.…”
Section: Observations In Soilsmentioning
confidence: 99%
See 2 more Smart Citations
“…This simplification ignores partitioning among solid, liquid, and gas phases in the unsaturated subsurface (vadose zone). While solid and liquid phase partitioning retard 14 C migration, gas phase partitioning is expected to increase vadose zone 14 C mobility (Thorstenson et al 1983). Thus, a more realistic prediction of vadose zone 14 C migration would include multiphase partitioning and the effect of geochemistry on partitioning and transport.…”
Section: Introductionmentioning
confidence: 99%